A modifier screen in the Drosophila eye reveals that aPKC interacts with Glued during central synapse formation - Ma Lisha; Johns Louise; Allen Marcus (BMC Genetics, 2009)
Abstract Background The Glued gene of Drosophila melanogaster encodes the homologue of the vertebrate p150Glued subunit of dynactin. The Glued1 mutation compromises the dynein-dynactin retrograde motor complex and causes disruptions to the adult eye and the CNS, including sensory neurons and the formation of the giant fiber system neural circuit. Results We performed a 2-stage genetic screen to identify mutations that modified phenotypes caused by over-expression of a dominant-negative Glued protein. We screened over 34,000 flies and isolated 41 mutations that enhanced or suppressed an eye phenotype. Of these, 12 were assayed for interactions in the giant fiber system by which they altered a giant fiber morphological phenotype and/or altered synaptic function between the giant fiber and the tergotrochanteral muscle motorneuron. Six showed interactions including a new allele of atypical protein kinase C (aPKC). We show that this cell polarity regulator interacts with Glued during central synapse formation. We have mapped the five other interacting mutations to discrete chromosomal regions. Conclusion Our results show that an efficient way to screen for genes involved in central synapse formation is to use a two-step strategy in which a screen for altered eye morphology precedes the analysis of central synaptogenesis. This has highlighted a role for aPKC in the formation of an identified central synapse.